The results of a clinical and neurophysiological study of the effectiveness of Parkon spray in the treatment of Parkinson's Disease (PD) - Gekht BM; Goldstein NI (Open Journal of Parkinson's Disease and Treatment - Peertechz Publications, 2022)
For more than 25 years, we have begun an experimental study of the physiological effect of micromolar concentrations of reactive oxygen species on the regulatory functions of the central nervous system. We found that these effects extend to the CNS centers and hormonal regulation of the hypothalamus and pituitary gland [1-4], as well as in the control of BBB permeability [5].